A minimal-order servo compensator includung disturbance rejection - Wurmthaler, Christoph; Hippe, Peter (at - Automatisierungstechnik, 1981)

A simple method to design state controllers with disturbance rejection - Wurmthaler, Christoph; Hippe, Peter (at - Automatisierungstechnik, 1981)

Automatic lateral vehicle guidance using tracking control - A modular approach to separate driver- and vehicle-dependent dynamics - Roppenecker, Günter; Wurmthaler, Christoph; Meier, Gerald (2004 IEEE Intelligent Vehicles Symposium, 2004)
In this contribution tracking control is applied to the lateral guidance of vehicles. An advantage of this approach is a separation between the control scheme depending on the dynamics of the specific vehicle and the trajectory generation. The latter one consists of an idealized model which does not contain any vehicle-specific parameters; the dynamics of the lateral guidance are assigned by a model feedback independent of the vehicle dynamics on the basis of the desired driving behavior. The control scheme has to be adapted to each type of vehicle; if the dynamics of the vehicle is known, this can be done systematically with respect to control engineering aspects.

Automatische Fahrzeug-Längsführung mittels Trajektorien- Folgeregelung: Ein modulares Konzept zur Trennung zwischen Fahrzeug- und Fahrer-Spezifika - Meier, Gerald; Roppenecker, Günter; Wurmthaler, Christoph (2004)

Comments on 'a regulating and tracking pi(d) controller' - Wurmthaler, Christoph; Hippe, Peter (International Journal of Control, 1987)

Comments on "Dynamic compensation method for multivariable control systems with saturating actuators" - Wurmthaler, Christoph; Hippe, Peter; et al. (IEEETransactions on Automatic Control, 1996)

Design of Optimal State Controllers in the Frequency Domain - Wurmthaler, Christoph; Hippe, Peter (at - Automatisierungstechnik, 1987)

Longitudinal vehicle guidance using neural networks - Wurmthaler, Christoph; Meier, Gerald; et al. (2005 IEEE International Symposium on Computational Intelligence in Robotics and Automation CIRA 2005, 2005)
Keywords: Longitudinal; Modelling; Neural networks; Simulation; Vehicle guidance

Model based feed forward control for measurable disturbances - Wurmthaler, Christoph; Kühnlein, Alexander (At-Automatisierungstechnik, 2009)
Keywords: Feed forward control; Measurable disturbances; Model based

Modellbasierte Steuerungsberechnung für Doppelkupplungsgetriebe als Teil eines neuen Gesamtkonzepts zur Getriebesteuerung und -regelung - Michalka, Andreas; Roppenecker, Günter; Wurmthaler, Christoph; Orend, Ralf (VDI-Berichte Nr. 2009, 2008)

Modellbasierte Steuerungsberechnung für Doppelkupplungsgetriebe als Teil eines neuen Gesamtkonzepts zur Getriebesteuerung und - regelung - Michalka, Andreas; Roppenecker, Günter; Wurmthaler, Christoph; Orend, Ralf (At-Automatisierungstechnik, 2009)
This paper presents a model based concept for controlling powertrains with dual clutch transmission in passenger cars. It focuses a feedforward control approach for shift actions by applying a simple vehicle model. Both types of possible shift actions are considered: those with start and target gear on different input shafts (direct shift) as well as those with start and target gear on the same input shaft (indirect shift). © Oldenbourg Wissenschaftsverla
Keywords: Dual clutch transmission; Feedforward and feedback control of powertrain; Model based approach; Powertrain management

Optimal reduced-order estimators in the frequency domain: The discrete-time case - Hippe, Peter; Wurmthaler, Christoph (International Journal of Control, 1990)

Systematic closed-loop design in the presence of input saturations - Wurmthaler, Christoph; Hippe, Peter (Automatica, 1999)